Power optimizer powerline communication system for smart hybrid dc-grid - Paul, Rimson (2014)
This report describes the development of a powerline communication system for power optimizers used in hybrid DC grid. Simple instructions are communicated through this power line monitoring system to provide monitoring and control. As clean energy is becoming more and more important in today’s world, more research is done on harvesting solar power which is a main source of clean energy. Since Singapore is very near to the equator the amount of solar energy available is high. As a small country it is important for us to harvest all the energy that is available to us. Several trial projects are undergoing before the commercial large scale launch of the technology in Singapore.